Patterns and trends of alcohol consumption in rural and urban areas of China: findings from the China Kadoorie Biobank - Im, PK; Millwood, I; Guo, Y; Du, H; Chen, Y; Yang, L; Chen, Z (BioMed Central, 2019)
Background In China, alcohol consumption has increased significantly in recent decades. Little evidence exists, however, about temporal trends in levels and patterns of alcohol consumption and associated factors in adult populations. Methods In 2004–08, the China Kadoorie Biobank recruited ~ 512,000 adults (41% men, mean age 52 years [SD 10.7]) from 10 (5 urban, 5 rural) geographically diverse regions across China, with ~ 25,000 randomly selected participants resurveyed in 2013–14. The self-reported prevalence and patterns (e.g., amount, beverage type, heavy drinking episodes) of alcohol drinking at baseline and resurvey were compared and related to socio-demographic, health and other factors. Results At baseline, 33% of men drank alcohol at least weekly (i.e., current regular), compared to only 2% of women. In men, current regular drinking was more common in urban (38%) than in rural (29%) areas at baseline. Among men, the proportion of current regular drinkers slightly decreased at resurvey (33% baseline vs. 29% resurvey), while the proportion of ex-regular drinkers slightly increased (4% vs. 6%), particularly among older men, with more than half of ex-regular drinkers stopping for health reasons. Among current regular drinkers, the proportion engaging in heavy episodic drinking (i.e., > 60 g/session) increased (30% baseline vs. 35% resurvey) in both rural (29% vs. 33%) and urban (31% vs. 36%) areas, particularly among younger men born in the 1970s (41% vs. 47%). Alcohol intake involved primarily spirits, at both baseline and resurvey. Those engaging in heavy drinking episodes tended to have multiple other health-related risk factors (e.g., regular smoking, low fruit intake, low physical activity and hypertension). Conclusions Among Chinese men, the proportion of drinkers engaging in harmful drinking behaviours increased in the past decade, particularly among younger men. Harmful drinking patterns tended to cluster with other unhealthy lifestyles and health-related risk factors.